2017
DOI: 10.1515/pjvs-2017-0027
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine profiles of dendritic cells (DCs) during infection with bovine leukaemia virus (BLV)

Abstract: BLV is an agent of enzootic bovine leukaemia (EBL), an infectious disease affecting cattle worldwide. BLV infection has been associated with immune system disorders and discrepancies in the cytokine network. The significance of dendritic cells in the pathogenesis of BLV infection is largely unknown, but considering their fundamental role in immune response it may be crucial. DCs precursors were isolated with the use of immunomagnetic beads from BLV-infected and BLV-free cows. From these precursors cultures of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The transcription level of IL-12 (p40) mRNA is significantly increased in the PBMC of AL cattle, while it is significantly decreased in PL cattle [198]. Furthermore, BLV infection activates the MoDc group, leading to a reduction in the expression levels of both IL-12 (p40) and IL-12 (p70) genes, which promotes the process of BLV infection [199,200]. BLV infection may also upregulate the expression of immunosuppressive molecules such as PD-L1, LAG-3, Tim-3, and CTLA-4 on the surface of PBMC through an unknown mechanism [201][202][203][204].…”
Section: Effects On the Function Of The Immune System Of Dairy Cowsmentioning
confidence: 99%
See 1 more Smart Citation
“…The transcription level of IL-12 (p40) mRNA is significantly increased in the PBMC of AL cattle, while it is significantly decreased in PL cattle [198]. Furthermore, BLV infection activates the MoDc group, leading to a reduction in the expression levels of both IL-12 (p40) and IL-12 (p70) genes, which promotes the process of BLV infection [199,200]. BLV infection may also upregulate the expression of immunosuppressive molecules such as PD-L1, LAG-3, Tim-3, and CTLA-4 on the surface of PBMC through an unknown mechanism [201][202][203][204].…”
Section: Effects On the Function Of The Immune System Of Dairy Cowsmentioning
confidence: 99%
“…IL-10 possesses immunosuppressive properties and can inhibit the transcription of Tax and pol genes during BLV replication in PBMC. Furthermore, it has been observed that the secretion of IL-10 increases with the progression of BLV infection [199].…”
Section: Effects On the Function Of The Immune System Of Dairy Cowsmentioning
confidence: 99%
“…Iwan et al [ 20 ] evaluated the effect of BLV infection on DC characteristics by taking bovine peripheral blood to isolate individual nucleated cells and isolating bone marrow dendritic cells (MDCs) from the individual nucleated cells, which were finally analysed using flow cytometry. The results showed that the level of IL-10 was significantly increased compared to the negative control group.…”
Section: Application Of Flow Cytometry In the Diagnosis Of Bovine Epi...mentioning
confidence: 99%